Accuracy of Self-Report Versus Objective Smart Scale Weights During a 12-Week Weight Management Intervention - Ross, Kathryn M. (Obesity (Silver Spring), 2019)
OBJECTIVE: Greater frequency of self-weighing has been associated with greater weight loss in weight management interventions, but little is known regarding accuracy of self-report weight data. METHODS: Agreement between objective smart scale and self-reported weight data was assessed in 74 adults (age=50.7 years, BMI=31.2 kg/m(2)) enrolled in a 12-week, Internet-based weight management program. Participants were asked to self-weigh daily using a study-provided smart scale and to self-report weights via the study website. RESULTS: There was strong agreement between smart scale and self-reported weight values, r(icc)=.982, but only moderate agreement between frequency of self-weighing assessed via each method, κ=.491, p<.0001. Greater self-weighing frequency was associated with greater weight loss across measures, ps<.001. Compared to days when they did both, weights were 0.66kg higher on days when participants self-weighed via smart scale but did not self-report weight (8% of days), and 0.58kg higher on days that they self-reported weight but did not self-weigh via smart scale (4% of days), ps<.0001. CONCLUSIONS: Results suggested that self-reported weight values are similar to smart scale measurements; however, either method alone may underestimate self-weighing frequency. Further, missing self-weighing data should not be treated as ignorable, as weights may be higher than those observed on non-missing days.